Nawrót guza mieszanego gruczołu łzowego – opis przypadku - Orzechowska-Wylęgała, Bogusława; Jędrzejewski, Piotr; Wylęgała, Edward; Stęplewska, Katarzyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Benign pleomorphic adenoma (mixed tumor) is the most frequently occurring tumor of epithelial origin. It occurs in serous glands, most frequently in parotid glands and rarely in small palatine glands, cheek glands, palatine tonsils and the lacrimal gland. This study is a description of the therapeutic management of a patient with recurrent pleomorphic adenoma of the lacrimal gland. In 1996, a 35 years old male patient underwent surgery to remove a tumor of the left orbit. Histopathological examination revealed pleomorphic adenoma. From 1998, the patient had observed increasing exophthalmus of the left eyeball. In 1999, vision distortion and headaches had begun. In 2005, from a cut along the upper-outer edge of the left orbit, an elastic and soft tumor 1 cm in diameter was removed from soft tissues of the upper eyelid. Then, with the use of the side orbitotomy technique, the orbit was opened through incision of the temporal muscle and removal of the orbital side wall. An eyelid nodule of 0.8 mm in diameter was removed together with an elastic and hard tumor of size 2.5 × 1 cm. The result of the histopathological examination of the palpebral tumor was pseudocystic tumor and of the orbital tumor was pleomorphic adenoma. Conclusion: patients resected for pleomorphic adenoma of the lacrimal gland require a long period of postoperative observation and periodic ophthalmologic examination.